Malawi : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in Malawi during the 1990s. Malawi's economy began to deteriorate in late 1991 as a result of a series of exogenous shocks. These shocks included two major droughts, a severe weakening in the terms of trade, and a suspension of donor nonhumanitarian aid owing to concern over governance. As a consequence, the average real GDP growth fell from 6 percent a year in 1989-91 to -3 percent a year in 1992-94. Savings and investment also fell considerably.